Perbedaan Efek Madu Akasia dengan Madu Multiflora terhadap Peningkatan Kadar Hemoglobin Remaja Putri - Rejeki Ratri Rahayu; Retno Widowati; Febry Mutiariami Dahlan (Institut Citra Internasional, 2023)
Adolescent girls’ anemia due to iron deficiency results in decreased learning achievement. Food intake is needed high in iron such as vegetables, animal protein, vegetable protein and honey. Honey is known to contain complete nutrition and can overcome anemia. Objective: To determine the differences between the provision of acacia honey and multiflora honey on the increasing of hemoglobin levels of adolescent girls at Posyandu Remaja Cetar Nusa Jaya subdistrict, Tangerang City in 2023. Methodology: The research design is quasy experiment. This research had been conducted during November 2022 - January 2023 at Posyandu Remaja Cetar with a population of 49 adolescent girls who experienced anemia. The techniques of sampling is purposive sampling and 40 people were recruited. The intervention group was given acacia honey while the control group was given multiflora honey for 14 days at a dose of 2x10 ml and keep drinking fe tablets once a week. Results: the average hemoglobin levels before and after provision akasia honey was 11.5 mg/dl and 12.46 mg/dl respectively. The average hemoglobin level before and after the administration of multiflora honey was11.39 mg/dl and 12.46 mg/dl respectively. Mann Whitney test was used to see the differences and shows the p value was 0.567 thatv > 0.05, so there was no difference of hemoglobin levels of adolescent girls after between acacia honey group and multiflora honey group after test. Conclusion: There is no difference of the increasing of hemoglobin levels among adolescent girls.